(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to see the effect of Self-Help Housing Stimulant Assistance (BSPS) on the welfare of low-income people. The data used is primary data obtained from a population of 84 beneficiaries of the self-help housing stimulant assistance program. The analysis method used is multiple linear regression. The results showed that food access and self-help housing stimulant assistance had a positive and significant effect on the welfare of low-income people in South Buru Regency